Model Pembelajaran Modifikasi Tingkah Laku Dan Implementasinya dalam Pendidikan Agama Islam - Haryati, Tati; Syahidin, Syahidin (PT. Student Rihlah Indonesia, 2023)
Behavioral modification-based learning model is considered necessary as it helps achieve learning outcome, that is to modify learners’ behavior to get expected personality. This model includes physical and biological aspects of learners. The model also requires a comprehensive and detail account of certain behaviors so that it can provide a comprehensive alternative to change the behavior. This literature study aims to explore how this behavioral modification-based learning model can be implemented in Islamic education. Data of the study are derived from relevant articles and books on behavioral modification and its relevance to Islamic education. Findings and analysis show that many aspects, principles, purposes, methods, and procedures of behavioral modification theory are applicable in the area of Islamic education. This is because the main of Islamic education is to change learners’ maladaptive behaviors into the adaptive and acceptable behavior. This modification is necessary to develop Muslim students with good characters.